Training & Sports - Sandau I; Witt M (Deutsche Zeitschrift für Sportmedizin, 2018)
Background: It is unclear what influence stress factors have on joint loading in weightlifting. The aim of this study was to show how barbell weight and repetition affect the joint loading on the ankle, knee and hip in order to estimate the strain on the corresponding joint actuators.Methods: Six male weightlifters underwent a test with snatch pulls. For the analysis, the 85% and 110% weight stage (1RM Snatch=100%) and the first and fourth repetitions with 100% weight were used. The joint loading was measured using inverse dynamics. Statistical analysis was based on t-test and effect size.Results: An increased weight on the barbell only leads to higher NJM impulse in the ankle (p = 0.013; d=1.47; very likely positive) and hip (p=0.010; d=1.78; very likely positive). The NJM impulse for the knee was not affected by barbell weight. An increased number of repetitions at 100% weight only reduced the NJM work at the ankle (p=0.000; d=-4.61; most likely negative).Discussion: The stress on individual joints depends on barbell weight and repetition. It can be assumed that this altered stress influences how joint actuators are strained and whatlocal training effect is obtained. Submaximal barbell weights with higher repetition rates are recommended for straining the knee joint actuators, while higher weights are necessary for exertingthe ankle and hip joint actuators. KEY WORDS: Snatch Pull, Stress, Strain, Joint Moment